2009
DOI: 10.1007/978-3-642-00549-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors in Brain Abscess

Abstract: Brain abscesses arise from a localized parenchymal infection, typically elicited by pyogenic bacteria such as S. aureus. Despite improvements in detection and treatment strategies, brain abscesses continue to occur, with an increased prevalence in developing countries and immune compromised patients. Adding to the seriousness of these infections is the recent emergence of antibiotic-resistant strains of bacteria, which are becoming more commonly associated with brain abscesses. Recent studies using a mouse exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…Recent studies have demonstrated the role of TLRs in orchestrating an inflammatory cascade in various models of CNS infectious diseases (28,31), including bacterial meningitis (30), brain abscess (19,44), and viral (59) and parasitic infections (38). We have shown that TLR2 is upregulated within 1 to 2 days in the CNS of mice infected i.c.…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies have demonstrated the role of TLRs in orchestrating an inflammatory cascade in various models of CNS infectious diseases (28,31), including bacterial meningitis (30), brain abscess (19,44), and viral (59) and parasitic infections (38). We have shown that TLR2 is upregulated within 1 to 2 days in the CNS of mice infected i.c.…”
Section: Discussionmentioning
confidence: 85%
“…This may trigger the release of self-antigens or DAMPs, many of which would not typically be exposed to the extracellular milieu. For example, during CNS infection, TLRs might play a dual role in ligand recognition, first by facilitating responses to the inciting pathogen and upon tissue destruction, recognizing newly liberated self-antigens, a scenario termed the “pathogen-necrosis-autoantigen triad” [100]. Newly liberated self-antigens may serve as direct triggers for TLRs to perpetuate the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pathophysiological processes occur during brain abscess development, including necrosis, apoptosis, and robust parenchymal inflammation (Stenzel et al. 2005b; Esen and Kielian 2009). One of the main pro‐inflammatory cytokines that is essential for generating a protective CNS anti‐bacterial immune response is IL‐1β (Kielian et al.…”
Section: Discussionmentioning
confidence: 99%